Costing of helicopter emergency services a strategic simulation based on the example of a German rural region - Johann Röper; Markus Krohn; Steffen Fleßa; Karl-Christian Thies (Health Economics Review, 2020)
Background: Helicopter emergency services (HEMS) are of increasing relevance for emergency medical services (EMS) of developed countries. Despite the known cost intensity of HEMS, there is only very limited knowledge of its cost dynamics and structures. This averts an efficient resource allocation of scarce EMS resources in an environment that is characterized by socio-political, medical and economic challenges. The objective of this study is the exemplary modeling of HEMS cost structures. Methods: We defined three scenarios with each five variations to illustrate different models of HEMS provision. Into these, we included varying availability times, technical features for off-shore or alpine rescue and differing numbers of operations. Cost data is based on a broad literature review and primary data from a German HEMS organization resulting in a cost function. We calculated average costs per primary missions and total costs, whilst differentiating between fixed, jump-fixed, variable and maintenance costs for every scenario variation. The costs were further used to evaluate the profitability of operations by executing a break-even analysis. Results: Average costs per HEMS operation decrease with increasing number of operations due to the digression of fixed costs. Depending on special equipment, availability times or other assumptions, total costs differ significantly with the different scenario variations. For the basic scenario (12 h of operations per day), the total costs per year of HEMS are 1,697,546.20 exteuro and the unit costs are 763.41 exteuro per primary mission at 1200 primary and 92 secondary operations. At an engine-runtime based revenue of 70 exteuro per minute, global cost covering is possible after 728 missions (c.p.). Conclusions: Considering a revenue of 70 exteuro per minute of engine run-time, HEMS can be operated at a profit for companies. However, the necessary remuneration represents a high financial effort for the societal cost bearers of helicopter emergency services. This leads to the question of the cost-benefit ratio of HEMS, which could be approached in further researches by using this model. The valuation of mission costs also opens a new view to the framework of HEMS disposition procedures and criteria. This cost analysis enhances the necessity of better planning of HEMS networks to use available resources efficiently in order to improve social welfare.
Keywords: 330